1995
DOI: 10.1073/pnas.92.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical signals by nervous systems.

Abstract: Intraspecific and interspecific communication and recognition depend on olfaction in widely diverse species of animals. Olfaction, an ancient sensory modality, is based on principles of neural organization and function that appear to be remarkably similar throughout the zoosphere.Thus, the "primitives" of olfactory stimuli that determine the input information of olfaction, the kinds of "molecular images" formed at various levels in the olfactory pathway, and the cellular mechanisms that underlie olfactory info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 65 publications
3
103
0
Order By: Relevance
“…In the olfactory systems of terrestrial animals, olfactory receptor neurons extend dendrites into an aqueous phase (vertebrate nasal mucus or insect sensillar lymph) that protects them from desiccation (Farbman, 1992;Hildebrand, 1995). It is not known how hydrophobic odorant molecules traverse these aqueous barriers to reach the odorant receptors.…”
mentioning
confidence: 99%
“…In the olfactory systems of terrestrial animals, olfactory receptor neurons extend dendrites into an aqueous phase (vertebrate nasal mucus or insect sensillar lymph) that protects them from desiccation (Farbman, 1992;Hildebrand, 1995). It is not known how hydrophobic odorant molecules traverse these aqueous barriers to reach the odorant receptors.…”
mentioning
confidence: 99%
“…Rast & Bräunig (1997) have shown that the motor neurones innervating the mandibular adductor and abductor muscles of Locusta fire in a pattern that resembles their activity during feeding even in an isolated suboesophageal ganglion, when the ganglion is bathed in pilocarpine. Not only are the mandibular motor neurones activated, so are those innervating the salivary glands and some neurosecretory cells that are normally active during feeding (Schachtner & Bräunig, 1993, 1995. These results indicate that mandibular movement and some associated activities are driven by a pattern generator in the mandibular neuromere of the suboesophageal ganglion.…”
Section: The Gustatory Systemmentioning
confidence: 61%
“…The arrangement of the olfactory system and the contrasting lack of a discrete centre for the gustatory system are common to all animals (e.g., Hildebrand, 1995) and reflect their different functions. The olfactory system is concerned with the perception of a broad array of chemical stimuli which may have ecological relevance.…”
Section: Insect Chemosensory Systemsmentioning
confidence: 99%
“…There are a number of known examples in which olfaction is known to play a significant role in the behaviour of insects. Some of the more interesting are: The malarialvector mosquito Anopheles gambiae detects their human host by body odours and CO 2 (Takken, 1996); the males of the sphinx moth Manduca sexta use pheromones released by female to find mates (Hildebrand, 1995); the honeybee Apis mellifera learns different odours to form navigational memories and use them for foraging behaviour (Galizia and Menzel, 2000;Reinhard et al, 2004); and parasitic wasps, such as Microplitis croceipes, detect odours produced by plants in response to host feeding (Lewis and Takasu, 1990).…”
Section: Introductionmentioning
confidence: 99%